EXPERIENCE OF DESIGNING AND CONSTRUCTION OF BALDACHINS OVER THE BUILDING (Collection of scientific works «Modern structures of metal and wood», 2020)
The  current  state  of  the  issue  is  generalized,  research  objectives  are  set,  a methodology  has  been  developed  for  assessing  the  technical  condition  of  operating  structures of buildings and structures. An analysis of the existing methods made it possible to establish that there are no methods for calculating building structures brought to practical use, evaluating their technical condition and justifying the possibility of subsequent reliable operation after various influences, as well as under the condition of reconstruction with completion. A  procedure  is  proposed  for  assessing  the  technical  condition  and  bearing  capacity  of exploited structures during reconstruction. A  technique  has  been  developed  for  obtaining  the  determining  parameters  of  the  technical state of structures. It is envisaged that structures and elements throughout the entire life cycle as a result of aging, degradation, and other influences can consistently be in each of the four technical states. The results of the survey and assessment of the technical condition of the building structures of the existing building are presented, on the cover of which it was necessary to mount the canopy. The  design,  calculations,  manufacture  and  installation  of  load-bearing  steel  and  enclosing structures of the canopy over the coating of the existing  building were carried out in connection with the need to protect the technological equipment and automobiles located on the coating from atmospheric precipitation and other climatic factors. The canopy is a one-story spatial frame, consisting of columns and trusses rigidly connected to  reinforced  concrete  structures,  based  on  the  column  heads.  The  connection  of  trusses  with columns is rigid and articulated. The system of ties along the columns and the coating provides the spatial rigidity of the structure. Based  on  the  calculations  performed  using  the  FEM  PC,  the  forces  in  the  elements  of  the computer model were determined, the necessary sections of the elements of the columns, trusses, runs, connections were established. The  manufacture, transportation and  installation of  structures were also performed. From the beginning of work to the commissioning of the facility a little more than 100 days passed.